PENDEKATAN RELASIONAL DALAM PERKEMBANGAN KARIR PERSPEKTIF ISLAM: SEBUAH KAJIAN SYSTEMATIC LITERATURE REVIEW - Eli Zerni; Yusra Meita; Masril Masril (STKIP Pesisir Selatan, 2026)
This study is motivated by the limitations of conventional career development theories that tend to emphasize individualistic orientations and therefore have not fully explained career decision-making dynamics within religious and collectivist societies. From an Islamic perspective, career development is influenced not only by personal abilities, but also by social relationships, family support, and spiritual values that shape individual life orientation. This study aims to examine the relational approach to career development from an Islamic perspective through a systematic review of previous studies. The research employed a Systematic Literature Review (SLR) method using the PRISMA approach on scientific articles published between 2015 and 2025 and obtained from Scopus, Google Scholar, and other relevant academic sources. Data were analyzed thematically through identification, screening, eligibility, and inclusion stages based on the research focus. The findings indicate that career development is influenced by family relationships, social support, emotional experiences, and the internalization of Islamic values such as trustworthiness, effort, consultation, and reliance on God. This study concludes that the integration of relational approaches and Islamic perspectives can serve as an alternative conceptual framework for developing more contextual, humanistic, and holistic Islamic career counseling.